-4.4951 * 10^9 is larger than 5.79 * 10^7.
So, when we subtract these two values, we subtract the larger value from the smaller value.
-4.4951 * 10^9 - 5.79 * 10^7 = -4.4951 * 10^9 - 0.579 * 10^9
Now, we can subtract the two values:
-4.4951 * 10^9 - 0.579 * 10^9 = -5.0741 * 10^9
Therefore, 5.79 * 10^7 - 4.4951 * 10^9 is equal to -5.0741 * 10^9.
5.79 * 10^7 - 4.4951 * 10^9
7 answers
1.4335 * 10^9
1.4335 * 10^9
sorry, i didnt finish the question
I apologize for the confusion. If you have any additional information or completed the question, please provide it so that I can assist you further.
1.4335 * 10^9 / 1.496 * 10^8
To divide these numbers in scientific notation, you need to divide the coefficients and subtract the exponents.
Step 1: Divide the coefficients:
1.4335 / 1.496 ≈ 0.957
Step 2: Subtract the exponents:
10^9 - 10^8 = 10^(9-8) = 10^1
Step 3: Rewrite the result in scientific notation:
0.957 * 10^1 = 9.57 * 10^0
Therefore, 1.4335 * 10^9 / 1.496 * 10^8 = 9.57 * 10^0
Step 1: Divide the coefficients:
1.4335 / 1.496 ≈ 0.957
Step 2: Subtract the exponents:
10^9 - 10^8 = 10^(9-8) = 10^1
Step 3: Rewrite the result in scientific notation:
0.957 * 10^1 = 9.57 * 10^0
Therefore, 1.4335 * 10^9 / 1.496 * 10^8 = 9.57 * 10^0